Bone mass in children and adolescents infected with human immunodeficiency virus - Luiz R.A. de Lima; Rosane C.R. da Silva; Isabela de C.B. Giuliano; Telma Sakuno; Sérgio M. Brincas; Aroldo P. de Carvalho (Brazilian Society of Pediatrics, 2013)
Objective: To describe bone mineral density (BMD) and bone mineral content (BMC) in children and adolescents infected with the human immunodeficiency virus (HIV), and to compare them with data from the National Health and Nutrition Examination Survey IV (NHANES IV). Method: The study included 48 children and adolescents (7 to 17 years old) infected with HIV through vertical transmission. BMC and BMD were measured by dual energy absorptiometry X-ray, by calculating z-scores based on data from NHANES IV. The information on clinical and laboratory parameters of infection by HIV was obtained from medical records. Physical activity, calcium intake, and skeletal maturation were also assessed. Descriptive and inferential statistical procedures were used, with levels of significance set at 5%. Results: Seropositive patients presented lower values compared to data from NHANES IV in all z-scores of bone mass (mean = −0.52 to −1.22, SD = 0.91 and 0.84, respectively). Based on the subtotal z-BMD, there was a prevalence of 16.7% of children and adolescents with low bone mass for age. Individuals using protease inhibitors presented a lower total z-BMD when compared to the group that did not use (−1.31 vs. −0.79, p = 0.02). There were no bone mass differences in relation to physical activity and calcium intake. Conclusions: In the present sample children and adolescents living with HIV have low bone mass for age, and the use of protease inhibitors appears to be related to such decreases.